Laboratory evaluation of FCC commercial catalysts. Analysis of products of industrial importance - Passamonti, Francisco Javier (2008)
The results of the conversion of a VGO over six equilibrium commercial FCC catalysts with different formulations in a batch CREC Riser Simulator laboratory reactor at 500 and 550 °C, catalyst to oil ratio 6.1 and reaction times from 3 to 30 s, were analyzed. It was possible to define the main catalyst characteristics in terms of various evaluation items, such as activity, gasoline yield and quality, LPG yield and coke yield, or the yields of particular compounds like, e.g., isobutane. Important differences in activity between catalysts were not observed, but catalyst properties reflected clearly as significant differences in gasoline, LPG or coke selectivities. Particularly, catalyst's hydrogen transfer properties impacted on gasoline composition and isobutane yield. The results showed that the CREC Riser Simulator reactor is an important tool for the evaluation of both commercial catalysts and feedstocks and process conditions.